Frequency of Early Refills for Opioids in the United States. Issue 9 (11th June 2020) - Kern, David M; Cepeda, M Soledad; Salas, Maribel; Phillips, Syd; Secrest, Matthew H; Wedin, Gregory P
Abstract: Objective: Refilling an opioid prescription early is an important risk factor of prescription opioid abuse and misuse; we aimed to understand the scope of this behavior. This study was conducted to quantify the prevalence and distribution of early refills among patients prescribed opioids. Methods: We conducted a retrospective cohort study utilizing dispensed prescription records. Patients filling one or more prescription opioids were identified and followed for one year. Early refills were defined as having a second prescription filled ≥15% early relative to the days' supply of the previous prescription for the same opioid (according to the National Drug Code [NDC]). The distribution of the number of early refills and patient characteristics were assessed. Results: A total of 60.6 million patients met the study criteria; 28.8% had two or more opioid prescriptions for the same opioid during follow-up. Less than 3% of all patients receiving an opioid had an early refill. Approximately 10% of those with two or more opioid prescriptions for the same drug had an early refill. For patients with multiple fills (N = 1.5 million with extended-release long-acting [ER/LA] opioids; N = 17.1 million with immediate-release short-acting [IR/SA] opioids), early refills were more common among patients with an ER/LA opioid (18.5%) compared with an IR/SA opioid (8.7%). Three-quarters of patients with an early refill had only one (70.9% and 78.4% for ER/LA and IR/SA, respectively). Conclusion: Refilling an opioid prescription with the same opioid early is an infrequent behavior within all opioid users, but more common in ER/LA users. Patients who refilled early tended to do so just once.